2006
DOI: 10.1055/s-2006-923833
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the V·O2max Plateau Phenomenon in World-Class Cyclists

Abstract: We aimed to determine the frequency of the VO2max plateau phenomenon in top-level male professional road cyclists (n = 38; VO2max [mean +/- SD]: 73.5 +/- 5.5 ml.kg(-1).min(-1)) and in healthy, sedentary male controls (n = 37; VO2max: 42.7 +/- 5.6 ml.kg(-1).min(-1)). All subjects performed a continuous incremental cycle-ergometer test of 1-min workloads until exhaustion. Power output was increased from a starting value of 25 W (cyclists) or 20 W (controls) at the rate of 25 W.min(-1) (cyclists) or 20 W.min(-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
3
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 30 publications
6
68
3
13
Order By: Relevance
“…[37][38][39] In the present study, the test was considered to have reached the maximum when the soccer players attained 2 of the following validation criteria: 1) maximum respiration exchange ratio (RER) ≥ 1.10; 2) Borg´s scale of subjective perception of tiredness ≥ 18 and 3) maximum heart rate ≥ 95% of the maximum chronotropic response predicted for the age. 8,[40][41][42] The criterion used for ascertaining VO 2max was an increase in VO 2 less than 2.0 mLkg -1.…”
Section: Logistics Of the Testsmentioning
confidence: 99%
“…[37][38][39] In the present study, the test was considered to have reached the maximum when the soccer players attained 2 of the following validation criteria: 1) maximum respiration exchange ratio (RER) ≥ 1.10; 2) Borg´s scale of subjective perception of tiredness ≥ 18 and 3) maximum heart rate ≥ 95% of the maximum chronotropic response predicted for the age. 8,[40][41][42] The criterion used for ascertaining VO 2max was an increase in VO 2 less than 2.0 mLkg -1.…”
Section: Logistics Of the Testsmentioning
confidence: 99%
“…It has been suggested that the plateau incidence is associated with the individual capacity to support high levels of fatigue and its resistance to pain 16 . However, highly trained athletes, which are familiarized with high levels of e ort and pain sensation during training session and/or competitions, did not show higher incidence of plateau 21,25 , strengthening the idea of other intervening variables. P et al 17 have suggested that the incapacity to reach plateau in incremental test is due to the incapacity to support the high power levels demanded during the test nal stages.…”
Section: Discussionmentioning
confidence: 84%
“…Studies in highly trained athletes showed similar or even lower percentage of plateau incidence as in the present study. Lucia et al 25 reported a plateau incidence of 47% in elite professional cyclists, whereas D 21 showed a plateau incidence of 25% and 39% for men and women, respectively in Olympic athletes runners of medium and long distance. In the present study, ve out of nine subjects presented plateau.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…He exercised to exhaustion and stopped when he reached maximal effort and fatigue as evidenced by perceived exertion . His VO 2 max (which corresponded to a speed of 20.3 km/h) was 80.4 ml·kg -1 ·min -1 , while criteria of maximal effort attainment were met (maximal value of HR of 187 beats/min, blood lactate concentration at end-exercise of 11 mmol/L, and respiratory exchange ratio > 1.1) (Lucia et al 2006). The running speed eliciting the LT was 19 km/h.…”
Section: Physiological Variablesmentioning
confidence: 99%